TREND WISATA UMRAH: ANTARA MENELADANI SUNNAH DAN TURISME SPIRITUAL - Dewi, Subkhani Kusuma (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2017)
Spiritual tourism though factually is not a new phenomenon, but a perspective in the perspective of sociology of religion gets its place, especially when tourism becomes a global trend of religious consumerism. In addition to Hajj, and rihlah, Umrah which is included in the journey of ziyarah is one of spiritual tourism trend. In practice spiritual tourism also infl uenced and infl uenced by religious discourse, including also understanding of what is called as sunnah. By using the concept of spiritual tourism taken from the perspective of sociology, this paper further utilizes the perspective of the umroh and haj travel bureaus on what is called the sunnah, where the umrah is one of them. The results of the analysis show that research that does not merely depart from popular culture shows the important role of travel agency forming a strategy in attracting pilgrims by not only binding umrah as a recreation / traveling, but also placing it as a worship. Keywords: Sunnah, Umrah, Spiritual Tourism